The Effect of Booklet Media Counseling on Increasing Knowledge of Disaster Risk Among Adolescents at Pancasila Islamic Boarding School - Herdiani, Tria Nopi; Sanisahhuri; Lora, Veky Puspa (Journal of Applied Nursing and Health, 2021)
Background: Indonesia is one of the countries with the highest disaster risk in the world, because according to the 2017 World Risk Index, Indonesia ranks 33rd in the world compared to other countries. According to data from the National Disaster Management Agency (BNPB), there were 2,572 natural disaster events in 2018 and 2,862 events in 2017. This study aims to determine the booklet media counseling on increasing disaster risk knowledge among adolescents at the Pancasila Islamic Boarding School in Bengkulu City Methods: This research is a quantitative study, using a pre-experimental design using a one group pets and posttest design. The population in this study were high school students of Pancasila Islamic Boarding School in grades 10 and 11 in science and social studies. There were 33 students. The sampling technique in this study used Accidental sampling Results: The results of the study were obtained: (1) Knowledge of the Pancasila Islamic boarding school students in Bengkulu city about the effect of booklet media counseling on increasing knowledge of disaster risk in adolescents Before being given booklet media, 31 people (93.9%) lacked knowledge and 2 people (6.1%) moderate knowledge. (2) Knowledge after high school students at Pancasila Islamic boarding school Bengkulu City About the effect of booklet media counseling on increasing knowledge of disaster risk in adolescents After being given a media booklet, 8 people (24.2%) lacked knowledge, 21 people (63.6%) had moderate knowledge and 4 people (12.1%) have good knowledge. (3) There is an effect of Knowledge of Media Booklet on increasing knowledge of Disaster Risk in adolescent students of Pancasila Islamic Boarding School Bengkulu City. Conclusion: Based on   results of research there is an effect of Knowledge of Media Booklet on increasing knowledge of Disaster Risk in adolescent students of Pancasila Islamic Boarding School Bengkulu City.